Factors associated with anemia in post-cesarean with and without COVID-19 at the Hospital Nacional Alberto Sabogal Sologuren - López Obando, Fanny Liliana (2022)
Objective. To know the intrinsic and extrinsic factors associated with anemia in post-cesarean women treated in the COVID-19 and non-COVID-19 obstetric area of the Alberto Sabogal Hospital. Methods. The study was observational, retrospective and cross-sectional, quantitative approach, explanatory level, casecontrol model, applied to 358 puerperal women; of which 179 were the cases, that is, those puerperal women with postpartum anemia and 179 were controls, taken from both areas. The data were processed with the SPSS 25 statistic. Results. The intrinsic factors: diet without variation, overweight or morbid obesity, parity of 4 or more, number of cesarean sections of 3 or more, and the intergenetic period of less than 2 years, were conditions that represented a double risk of producing anemia in the puerperium among women in the study, in relation to those who did not have these characteristics. Also, the intrinsic factor or condition of having had anemia during pregnancy, resulted in a 5 times greater probability of producing anemia in the puerperium among the women in the study (Odds Ratio 5.156), compared to the women who did not have anemia. Folic acid intake was 3.4 times less likely (Odds Ratio of 3.408) to develop anemia compared to those who did not, and complications in the immediate puerperium (Odds Ratio of 3.397) were associated with anemia in puerperal women. Conclusions. Intrinsic factors such as the diagnosis of anemia during pregnancy and extrinsic factors such as folic acid not ingest and complications in the immediate puerperium were associated with anemia in puerperal women in the COVID-19 and non-COVID-19 obstetric area of Hospital Alberto Sabogal.